Upaya Pengendalian Kenakalan Remaja di Sekolah Menengah Atas Negeri (SMAN) Kabupaten Kutai Timur dalam Perspektif Pendidikan Islam - Rahmawati, Indriana Rahmawati; Basith, Abdul (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
The purpose of this study is to explore information about the forms of juvenile delinquency, factors that influence the occurrence of juvenile delinquency, and the efforts made by the school in controlling juvenile delinquency. The object in this study is the State High School (SMAN) in East Kutai Regency: SMAN 1 Sangatta Utara and SMAN 1 Sangatta Selatan. The approach used in this study is a qualitative research approach, with data collection techniques using interviews, observation and documentation. The results of the study show that the form of juvenile delinquency is mostly a form of juvenile delinquency in the case of violating school rules and violating regulations in the community. The factors that cause delinquency are due to external factors and individual internal factors. Efforts that have been made by schools in controlling juvenile delinquency is by preventive, repressive and curative manner.